Dental management of a child with Joubert syndrome: a case report - Rafatjoo, Rezvan; Torkaman, Sima; daneshyar, fahimeh (Iranian Journal of Child Neurology, 2022)
Joubert syndrome is a rare type of autosomal recessive genetic disorder that the incidence of it has been estimated to be in 80000 -100000 live births. Brain magnetic resonance image (MRI) with molar tooth sign is sufficient for a definite diagnosis. Immediately after birth, the prognosis depends on the severity and extent of the respiratory disorder. In this case a 5-year-old boy with joubert syndrome was brought by his parents due to inability to chewing due to dental caries and toothache. According to the patient’s clinical condition and inability to cooperate his dental procedures were performed under anesthesia at the hospital. These patients are sensitive to the respiratory effects of anesthetics like opiate and nitrous oxide, therefore, they should not be used. In this patient we used sevoflurane gas to induce general anesthesia. Advanced dental caries are observed in the reported cases of this syndrome, which may be attributed to dental hypoplasia and the inability to observe dental and oral hygiene. Thus, the patients’ parents must be given necessary instructions on the observance of oro-dental hygiene and regular follow-ups should be done for dental check-ups and preventive measures.